2-Methyl-2,4-pentanediol (MPD) boosts as detergent-substitute the performance of ß-barrel hybrid catalyst for phenylacetylene polymerization - Kinzel, Julia; Sauer, Daniel F.; Bocola, Marco; Arlt, Marcus; Mirzaei Garakani, Tayebeh; Thiel, Andreas; Beckerle, Klaus; Polen, Tino; Okuda, Jun; Schwaneberg, Ulrich (Beilstein Journal of Organic Chemistry, 2017)
Covering hydrophobic regions with stabilization agents to solubilize purified transmembrane proteins is crucial for their application in aqueous media. The small molecule 2-methyl-2,4-pentanediol (MPD) was used to stabilize the transmembrane protein Ferric hydroxamate uptake protein component A (FhuA) utilized as host for the construction of a rhodium-based biohybrid catalyst. Unlike commonly used detergents such as sodium dodecyl sulfate or polyethylene polyethyleneglycol, MPD does not form micelles in solution. Molecular dynamics simulations revealed the effect and position of stabilizing MPD molecules. The advantage of the amphiphilic MPD over micelle-forming detergents is demonstrated in the polymerization of phenylacetylene, showing a ten-fold increase in yield and increased molecular weights.
Keywords: amphiphilic molecule 2-methyl-2,4-pentanediol; hybrid catalyst; phenylacetylene polymerization; refolding agents; transmembrane protein FhuA